PENGARUH CUSTOMER SATISFACTION DAN CUSTOMER TRUST TERHADAP CUSTOMER LOYALTY PRODUK KRIM PELEMBAB WAJAH FAIR & LOVELY - Dwi Wahyuni Rahma Wati; Naning Fatmawatie; Nilna Fauza (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2020)
The industry is required not only to conduct business activities to obtain new customers, but also to increase the loyalty of old customers or customer loyalty. This study aims to determine customer satisfaction, customer trust, and customer loyalty. In addition, it is also to find out the effect of customer satisfaction on customer loyalty, the influence of customer trust on customer loyalty, and the influence of customer satisfaction and customer trust on customer loyalty on students of Islamic Boarding School ar-Roudloh Kediri City simultaneously on Fair & Lovely facial moisturizing cream products. This research uses a descriptive quantitative approach. The population of this research is 107 students of Islamic Boarding School ar-Roudloh Kediri City, East Java. While the number of samples in this study were 65 students. The results showed that the customer satisfaction, customer trust, and customer loyalty of each student included in the category of